2019
DOI: 10.2147/clep.s194056
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bisphosphonates and primary breast cancer risk: an updated systematic review and meta-analysis involving 963,995 women</p>

Abstract: Importance Prevention of primary breast cancer (BCa) in women is of great public health importance. The existing results from observational epidemiologic studies focused on the association between bisphosphonates and primary BCa risk have been inconsistent. Objective To update this systematic review and meta-analysis to assess the effect of bisphosphonates on primary BCa risk. Data sources We comprehensively searched MEDLINE, EMBASE, Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
5
6
0
Order By: Relevance
“…However, the randomized control trials were not initially designed to study breast cancer outcome and they might be at high risk of selective reporting bias. Overall, systemic reviews and metaanalyses agreed upon a signi cantly decreased risk of primary breast cancer in bisphosphonates users [24][25][26]. This is in accordance with our ndings.…”
Section: Comparison Of Our Results With Other Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…However, the randomized control trials were not initially designed to study breast cancer outcome and they might be at high risk of selective reporting bias. Overall, systemic reviews and metaanalyses agreed upon a signi cantly decreased risk of primary breast cancer in bisphosphonates users [24][25][26]. This is in accordance with our ndings.…”
Section: Comparison Of Our Results With Other Studiessupporting
confidence: 91%
“…The entangled and far-reached regulatory network is summarized in Figure 1 Epidemiological studies have shown that bisphosphonates have variable non-adverse, e.g. protective or no related risk towards female breast cancer [15][16][17][18][19][20][21][22][23][24], although some reports showed that alendronate may be associated with higher risks in lung and liver cancers [25,26]. A recent study suggests a potential protective effect of denosumab ever use on breast cancer risk in a cohort of older women previously treated with bisphosphonates [27].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, systemic reviews and meta-analyses agreed upon a significantly decreased risk of primary breast cancer in bisphosphonates users [24][25][26]. This is in accordance with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, a systematic review and meta-analysis involving nearly 1 million women, that included many of the studies mentioned above, demonstrated that the use of bisphosphonates for >1 year was associated with a 12% decreased risk of primary breast cancer. 100 Similar findings were observed for denosumab where use was associated with a 13% decreased risk of developing breast cancer. 101 In women with early breast cancer, bisphosphonates were associated with a 14% reduction in the risk of bone metastases.…”
Section: Can the Treatment Of Endocrinopathies Reduce Recurrence Oversupporting
confidence: 63%